Era Beauty Spa Booking System - Hamid, Nur Aisyah Zayani; Mohd Nawi, Nazri (Applied Information Technology And Computer Science, 2025)
The Spa Booking System is a web-based platform created to improve and expedite the spa booking procedure. It offers clients and spa management a practical and effective platform that can help book spa treatments more convenient and more modernly. Spa managers profit from a centralized dashboard for scheduling and appointment management, while clients can conveniently explore spa services, check availability, and make appointments. The system provides business analysis therapist scheduling capabilities and automated alerts that show a lower number of no-shows. In the spa business, this approach increases productivity and improves client experience